Smart Trash Bin With Solar Cell - Mia Galina; Ulfa Dwinda Umar (President University, 2017)
Smart Trash Bin with Solar Cell is a device which can help the people to increase their awareness about environmental hygiene. With an automatic lid and volume level indicators, people do not need to touch the lid to open it and check whether the bin is already full or not. This smart trash bin will send alerts when they are getting full. If the first ultrasonic sensor detected an object, the automatic lid will be open, while the second ultrasonic sensor detect inside of the trash bin whether it is already half full, half-quarter full or totally full to trigger the indicator to start working. The automatic lid and volume level indicators will be implemented by using Arduino UNO program. And due to the eco-friendly consideration, this device uses a solar cell to produce power to activate it.Keywords: Smart Trash Bin, Ultrasonic Sensor, Servo Motor, Solar Cell, Environmental Awareness